Kardiochirurgia dorosłychAortic valve replacement with On-X 21 mechanical prosthesis in patients with small aortic root – 5 years’ experience - Perek, Bartłomiej; Paluszkiewicz, Lech; Misterski, Marcin; Sarnowski, Wojciech; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Aim: Evaluation of early and mid-term outcome after aortic valve replacement with On-X 21 mechanical prostheses in patients with small aortic root. Material and methods: This study involved 50 patients (pts) (33 men and 17 women) at the mean age of 61.6±7.6 years who underwent aortic valve replacement with On-X 21 prostheses between 2001 and 2004. All pts were operated on through a median sternotomy using cardiopulmonary bypass in moderate hypothermia (26-28°C). At the end of follow-up echocardiography was performed and prostheses’ performance was assessed (mean transvalvular gradient (PPG), effective orifice area (EOA) and its index (EOAi)). Results: Perioperative mortality was 2.0% (1 pt). During follow-up (mean duration time 41.7±9.6 months) completed by 47 pts (94.0%) the other three pts died. 12- and 48-month probability of survival was 94.0±3.4% and 91.8±4.0%, respectively. Nobody required reoperation; no cases of prosthetic valve infective endocarditis or perivalvular leakage were noted either. Estimated 12- and 48-month freedom from thromboembolic complications was 97.9±2.1% and 89.7±0.8%, and freedom from anticoagulant-induced haemorrhagic accidents was 97.9±2.1% and 95.5±3.1%, respectively. In the last follow-up outpatient clinic examination, 39 pts (90.7%) were in I or II NYHA functional classes. Implanted prostheses functioned properly with mean PPG 10.7±3.6 mmHg, and had EOA 1.73±0.59 cm 2 and EOAi 0.91±0.30 cm 2 /m 2 , respectively. Conclusions: Aortic valve replacement with On-X 21 mechanical prostheses in patients with small aortic root is associated with low mortality and good clinical as well as echocardiographic mid-term results.